Mandatory food information in case of short food supply chains and local food systems in EU and US legislation: a comparative study - Kapała, Anna; Lattanzi, Pamela (Przegląd Prawa Rolnego, 2021)
The study aims to identify what food information is required for the sale of food by farmers in short food supply chains (SFSCs) in EU law in accordance with Regulation (EU) 1169/2011 and legislation of selected Member States (Poland, Italy and France), which are allowed to adopt national measures in some issues. A comparison with US law serves as a benchmark for drawing conclusions, in particular, whether the requirements are appropriate and proportionate for SFSCs. The Regulation takes into account these alternative sales channels, as Art. 44 only requires information on allergens when offering unpackaged food for sale to final consumers or mass caterers, or when foodstuffs are packaged in the sales room at the consumer's request or packaged for direct sale. However, Member States have adopted national measures imposing an obligation to provide, in writing, more information on food in the direct sale, such as the ingredients list, but not the nutrition declaration. The US legislature is more restrictive, as it requires not only ingredient lists but also nutritional information for nearly all packaged and unpackaged food products, except for agricultural raw materials. The multitude of obligations imposed at various legislative levels is undoubtedly a challenge for farmers involved in SFSC, who are not prepared on a par with professional food companies to implement them.